TRANSFORMASI MOTIVASI BELAJAR SISWA MELALUI PEMBELAJARAN BERDIFERENSIASI BERBASIS TEORI BEHAVIORISTIK DI SEKOLAH DASAR - Tini Sudiar (Jurnal Genta Mulia, 2026)
Elementary school learning still faces the problem of low student motivation due to the implementation of teaching methods that tend to be uniform and teacher-centered. This condition requires learning innovations that can accommodate differences in students’ characteristics. One relevant approach is differentiated learning combined with behaviorist theory through the application of stimulus, response, and reinforcement. This study aims to analyze the implementation of behaviorist theory through differentiated learning and to examine the improvement in learning motivation among sixth-grade students at SD Negeri 27 Tanjungpandan. The research method used was a descriptive approach, with data collection techniques including observation and interviews with teachers and students. This study also provides practical implications for elementary school teachers in designing more varied and responsive learning experiences tailored to students’ needs. Teachers are expected to consistently integrate differentiation strategies with behaviorist principles to create more meaningful learning experiences. The results showed that the implementation of behaviorist-based differentiated learning was able to increase students’ activeness, perseverance, and interest in learning. This was indicated by increased student participation in classroom activities, greater confidence in answering questions, and higher enthusiasm in completing assignments. The provision of reinforcement in the form of praise and rewards proved effective in strengthening students’ positive learning behaviors. Adjusting tasks according to students’ abilities also enhanced their self-confidence and engagement in the learning process. Therefore, differentiated learning based on behaviorist theory has been proven effective in sustainably improving students’ learning motivation.